Biodegradable magnesium combined with distraction osteogenesis synergistically stimulates bone tissue regeneration via CGRP-FAK-VEGF signaling axis. (August 2021) - Ye Li,; Xu, Jiankun; Mi, Jie; He, Xuan; Pan, Qi; Zheng, Lizhen; Zu, Haiyue; Chen, Ziyi; Dai, Bingyang; Li, Xu; Pang, Qianqian; Zou, Li; et al.
Abstract: Critical size bone defects are frequently caused by accidental trauma, oncologic surgery, and infection. Distraction osteogenesis (DO) is a useful technique to promote the repair of critical size bone defects. However, DO is usually a lengthy treatment, therefore accompanied with increased risks of complications such as infections and delayed union. Here, we demonstrated that magnesium (Mg) nail implantation into the marrow cavity degraded gradually accompanied with about 4-fold increase of new bone formation and over 5-fold of new vessel formation as compared with DO alone group in the 5 mm femoral segmental defect rat model at 2 weeks after distraction. Mg nail upregulated the expression of calcitonin gene-related peptide (CGRP) in the new bone as compared with the DO alone group. We further revealed that blockade of the sensory nerve by overdose capsaicin blunted Mg nail enhanced critical size bone defect repair during the DO process. CGRP concentration-dependently promoted endothelial cell migration and tube formation. Meanwhile, CGRP promoted the phosphorylation of focal adhesion kinase (FAK) at Y397 site and elevated the expression of vascular endothelial growth factor A (VEGFA). Moreover, inhibitor/antagonist of CGRP receptor, FAK, and VEGF receptor blocked the Mg nail stimulated vessel and bone formation. We revealed, for the first time, a CGRP-FAK-VEGF signaling axis linking sensory nerve and endothelial cells, which may be the main mechanism underlying Mg-enhanced critical size bone defect repair when combined with DO, suggesting a great potential of Mg implants in reducing DO treatment time for clinical applications.